(untitled) (JOSAR (Journal of Students Academic Research), 2019)
This research is in the background by the low activity of students. The purpose of this research is to improve activities and by developing Pancasila values using video. This research uses Research and Development (R & D). Desaign and Development methods are also defined as a research method used to produce certain products, and test the effectiveness of the product. Data collection techniques by observing students’ interest in learning. The data collection tool is by means of a video concept observation guide. The collected data is then analyzed by analysis of research and development. The results of the research are shown on the material aspects and 4.2 on the media aspects 4.4 On aspects of the language 4.0 according to the module eligibility criteria that the module is appropriate to use. The validation results indicated that the module was able to influence students’ learning interest as much as 4.2. This is supported by student observation sheets that show interest in the use of the module as many as 6 students feel interested and helped in carrying out learning. It is hoped that this study will contribute towards development and progress to support the achievement of the FKIP UNISBA vision and mission.